Prevalence of latent Mycobacterium tuberculosis infection among professionals of the primary healthcare network - Tássia Silvana Borges; Eduardo Chaida Sonda; Alexandre Daronco; Fabiana Battisti; Marcos Moura Baptista Dos Santos; Andréia Rosane Moura Valim; Mariana Valença; Lia Gonçalves Possuelo (Universidade de Fortaleza, 2014)
Objective: To estimate the prevalence of latent M. tuberculosis infection and identify characteristics related to latent infection among workers of the primary healthcare network.Methods: Cross-sectional, observational and descriptive study, conducted in 2011, included 137 basic health workers who performed their activities in a municipality. Interviews were carried out addressing characteristics of exposure at work (BCG vaccination, length of time working in the health system, potential exposure to tuberculosis, HIV infection, use of corticosteroids, diabetes, use of tobacco or alcohol) and subsequently performed tuberculin skin test (TST). Data was analyzed with Fischer and Student's t-test (p < 0.05). Results: Health professionals were mostly women (n=126, 92%) with mean age of 35.3 (± 9.1) years. Among the reactors, 25 (55.5%) sought medical care, and of these, 7 (28%) underwent prophylactic treatment. The prevalence of latent tuberculosis was 32.8%. Of the characteristics evaluated, only smoking (OR 3.03; 95%CI 1.05-8.77) was associated with latent infection. Conclusion: The estimated prevalence of latent M. tuberculosis infection among the evaluated health workers was 32.8%. As for the characteristics studied, it was not possible to relate them to latent infection among workers in primary healthcare network, with the exception of the smoking habit. doi: 10.5020/18061230.2014.p269